Loop diuretic-induced hyponatremia: a case report - Kolasani, Bhanu Prakash; Shanthi, C. M. Divya; Sasidharan, Prasanand (International Journal of Basic & Clinical Pharmacology, 2016)
Hyponatremia is the most common encountered electrolyte abnormality where the serum sodium concentration is <136 mEq/L. The most common causes are either the concurrent illnesses or the medications. Diuretics top the list of drugs inducing hyponatremia and this occurs more frequent within 2 weeks of initiating therapy. Though thiazide diuretics are frequently the culprits of inducing hyponatremia, the role by/risk with loop diuretics cannot be ignored. Prompt diagnosis and management of hyponatremia needs a sound knowledge with which permanent neurologic sequelae and morbidity could be prevented. Here, we report a case of hyponatremia induced by loop diuretic and spironolactone combination, where the presenting complaints of the patient were only intractable nausea and altered taste. The patient was successfully managed with hypertonic saline and the vasopressin receptor antagonist, tolvaptan, which belongs to a new class of drugs called aquaretics.